al-Da'wah al-fardiyyah : discourse on its action plan - Bahari, Che Amnah; Faisal, Muhammad (International Islamic University Malaysia, 2011)
The al-da'wah al-fardīyyah seems to be very significant in making Islamic message reach the targets. Action plan of this technique has been developed by various scholars based on asan al-Banna’s thought. This action plan has been proven to be an effective one until today. This article focuses mainly on four dimensions of the issue: (1) the definition of al-da'wah al-fardīyyah, (2) the history of al-da'wah al-fardīyyah, (3) the differences between al-da'wah al-fardīyyah and al-'ummah, and (4) the current developments in the work of al-da 'wah and its action plan.